TRADITIONAL KNOWLEDGE AND PRACTICES OF THE QUILOMBOLA POPULATION IN HEALTH CARE AND THE TREATMENT OF DISEASES: AN INTEGRATIVE LITERATURE REVIEW - Revellyn Gabriely Bezerra da Silva; Aline Faria da Silva; Kassandra Santos Costa; Ana Carolina Silva do Nascimento; Cíntia Clávia Mallmann Lessa; Lane Souza da Silva; Ygor Gabriel Martins Dubois; Tayane Moura Martins (Artefactum - revista de estudos interdisciplinares, 2026)
Quilombolas are traditional peoples who hold their own concepts of health and utilize knowledge passed down through generations. Understanding these practices is fundamental to fostering interculturality in healthcare. This study aimed to describe the traditional knowledge and practices of the Brazilian quilombola population regarding healthcare and the treatment of illnesses. It is an exploratory and descriptive integrative literature review with a qualitative approach, based on articles published between 2005 and 2025 in the CAPES, PubMed, and Google Scholar databases. Twenty-six studies were selected and grouped into three thematic categories addressing traditional health and illness practices and knowledge: plants used and their therapeutic indications; methods of plant acquisition and preparation; and dietary practices as health promoters. The results highlighted the use of medicinal plants and specific dietary habits, as well as the role of beliefs and religiosity. The study emphasized the importance of the historical and cultural context of these practices, as well as the need for respect and appreciation from healthcare services, thereby contributing to raising professional awareness and adapting care to be more culturally appropriate.